Review of the distribution and new occurrences of Lacunicambarus thomai (Jezerinac, 1993) (Decapoda, Cambaridae) in Pennsylvania and its possible introduction outside of its native range - Patrick F. Allison Jr. (Pensoft Publishers, 2021)
Recent investigations into the distributions of western Pennsylvania, USA, crayfishes have yielded 30 new occurrences of Lacunicambarus thomai (Jezerinac, 1993). The discovery of a population of L. thomai in Crawford County is the furthest north population in the state. Two populations of L. thomai were discovered outside of its historic range in Fayette and Somerset counties in southwestern Pennsylvania. These populations are in recreational fishing destinations and may have been introduced by bait bucket or construction fill. Additional surveys for Pennsylvania L. thomai should occur in areas lacking recent, thorough searches.